International sanctions and coups d'état - Pascal Langer (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
This paper investigates the relationship between international sanctions and coups d'état in targeted countries. Employing a panel logit model and utilizing data from 1972 to 2013 drawn from the Global Sanctions Database and the Coup Leaders Dataset, we analyze the effects of UN and Western sanctions on both occurrence of coups and successful coups. Western sanctions are found to initially increase the likelihood of coups by more than 4.0 pp with a diminishing impact over time. In the post-Cold War era, Western sanctions raise the probability of coups by 1.7 pp and successful coups by even 2.1 pp. The effects are particularly pronounced in non-democratic regimes, especially in personalist authoritarian regimes.
Keywords: D74; F51; H56; 330; International Sanctions; Coups d'État